Application Of C4.5 Model Inpatient Medical Record Information System Based on ICD-10 Diagnosis Classification : Case Study of Uni’s Dental Care - Mardiansyah, Kalsi Kireina; Hamdani, Mohammad; Rachman, Rizal; Suciyono, Nanang; Sudarsono, Nono (Electronic, Business, Management and Technology Journal, 2024)
Dental medical records may consist of written documentation with comprehensive and precise details regarding patient identity, diagnosis, medical history, ICD-10 disease codes, medical procedures, and examination result documentation. Nonetheless, issues frequently arise when the documentation of medical records remains manual. This results in prolonged data searches and frequent loss or damage of files due to disorganized storage. The employed research method is descriptive. Data gathering methods are conducted through observation and interviews. The system development methodology pertains to the waterfall model. The calculation stages can be established in the system's design and development utilizing the Object-Oriented Analysis and Design (OOAD) methodology. A patient medical record information system was developed utilizing the ICD-10 diagnosis classification, accessible to physicians and administrators remotely. This web-based system was constructed using the PHP programming language, with Visual Studio Code as the code editor, XAMPP as the web server, and MySQL as the database management system. This patient medical record website is anticipated to enable administrators and physicians to input, modify, read, and search for patient data and medical records based on examination results. It will be accessible at any time and from any location. This website can forecast the potential danger of a patient's illness depending on the patient's symptoms.